Systematic Review of the Combined Treatment of Endo, Ortho and Prosthesis in Maxillary Central Fracture Based on Surgical Points - Sajedeh Safari; Anahita Dehghani Soltani; Mohammad Amin Bafandeh; Amir Abolhasani Zratcar; Qaderi, Nadieh (Galen Medical Journal, 2024)
Background: The present study systematically investigated the combined treatment of endo, ortho and prosthetics in maxillary central fractured teeth based on surgical points. Materials and Method: In the current study, the issue was investigated by reviewing 39 articles and considering key words such as: "Combined endo, ortho and prosthetic treatment", "Central fractured tooth", "Upper jaw", "Surgical tips". The treatment of root-treated teeth whose crown structure has suffered severe destruction has always been considered. Results: The results of the recent study showed that the angles that in single units will cause the access hole to be placed in the buccal and in bridges will cause the prosthesis to be locked in the connections. Conclusion: Composite blinds along with cemented tooth-colored dowels are commonly used to restore root-treated teeth, and many studies have been done on the mechanical properties and to some extent micro leakage of these restorations. One of the main causes of failure in restorative treatments for endodontic teeth with extensive destruction is the reduction of tooth fracture resistance and restoration.